MENINGKATKAN MOTIVASI DAN KETRAMPILAN PROSES SAINS MELALUI KERJA ILMIAH BERTANYA PADA KONSEP SISTEM KLASIFIKASI TUMBUHAN DALAM PENERAPAN KURIKULUM 2013 DI SISWA SMP KELAS VII AMBON - Pamella Mercy Papilaya (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: The concept of classification of living things, especially the determination key materials, is one of the concepts in learning biology is quite difficult to understand by students. The concept of learning in the classroom tend to use traditional approaches in the form of lectures and experiments. Questioning skills very important to have a teacher, because it can increase student participation in the learning activity, generate interest and curiosity, develop ways of thinking and active learning, and focus on students. Methods: This study was conducted using the Class Action Research (PTK) is carried out in collaboration with the seventh grade biology teacher and vice principal at Junior High School Curriculum affairs 6 Ambon. PTK is held in the classroom while the class VII1 VII2 used as a test model of learning. Results: The results showed that apply the concepts and principles in biology through scientific work asked to improve the performance of teachers. Application of scientific work asks improve student learning outcomes. Application of scientific work asks improve student motivation. Application of scientific work asked to create a climate conducive learning and Application of scientific work asks improve students' science process skills. Conclusions: The implementation of learning in the classroom that teachers must practice more to phrase questions to reveal the facts, prepare questions about the procedure, prepare questions about the reasons for the use of certain tools or materials and prepare questions for designing a scientific activity.